CD36 (SR-B2) as a Target to Treat Lipid Overload-Induced Cardiac Dysfunction - Jan F.C. Glatz; Joost J.F.P. Luiken; Miranda Nabben (Journal of Lipid and Atherosclerosis, 2020)
The heart faces the challenge of adjusting the rate of fatty acid uptake to match myocardial demand for energy provision at any given moment, avoiding both too low uptake rates, which could elicit an energy deficit, and too high uptake rates, which pose the risk of excess lipid accumulation and lipotoxicity. The transmembrane glycoprotein cluster of differentiation 36 (CD36), a scavenger receptor (B2), serves many functions in lipid metabolism and signaling. In the heart, CD36 is the main sarcolemmal lipid transporter involved in the rate-limiting kinetic step in cardiac lipid utilization. The cellular fatty acid uptake rate is determined by the presence of CD36 at the cell surface, which is regulated by subcellular vesicular recycling from endosomes to the sarcolemma. CD36 has been implicated in dysregulated fatty acid and lipid metabolism in pathophysiological conditions, particularly high-fat diet-induced insulin resistance and diabetic cardiomyopathy. Thus, in conditions of chronic lipid overload, high levels of CD36 are moved to the sarcolemma, setting the heart on a route towards increased lipid uptake, excessive lipid accumulation, insulin resistance, and eventually contractile dysfunction. Insight into the subcellular trafficking machinery of CD36 will provide novel targets to treat the lipid-overloaded heart. A screen for CD36-dedicated trafficking proteins found that vacuolar-type H+-ATPase and specific vesicle-associated membrane proteins, among others, were uniquely involved in CD36 recycling. Preliminary data suggest that these proteins may offer clues on how to manipulate myocardial lipid uptake, and thus could be promising targets for metabolic intervention therapy to treat the failing heart.